2023
DOI: 10.1111/jpi.12858
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin mediates elevated carbon dioxide‐induced photosynthesis and thermotolerance in tomato

Abstract: Increasing carbon dioxide (CO2) promotes photosynthesis and mitigates heat stress‐induced deleterious effects on plants, but the regulatory mechanisms remain largely unknown. Here, we found that tomato (Solanum lycopersicum L.) plants treated with high atmospheric CO2 concentrations (600, 800, and 1000 µmol mol−1) accumulated increased levels of melatonin (N‐acetyl‐5‐methoxy tryptamine) in their leaves and this response is conserved across many plant species, including Arabidopsis, rice, wheat, mustard, cucumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…AtOMT3 is defined as AtASMT1, which increases melatonin levels, improves plant salt tolerance, and is closely related to Pst DC3000 resistance ( Shi, Wei & He, 2016 ; Zheng et al, 2017 ). AtOMT6 is an OMT protein on class II OMT protein that shows close homology with CmOMT8 and has been identified as AtCOMT1, which is associated with melatonin synthesis, regulating melatonin synthesis levels, and improving resistance to multiple stresses in plants, such as salt stress and heat stress ( Zheng et al, 2017 ; Hasan et al, 2023 ). In contrast, Chang et al (2021) reported that ClCOMT1 ( ClOMT3 ) is also closely homologous to CmOMT18 and could enhance abiotic stress resistance in Arabidopsis by increasing endogenous melatonin content.…”
Section: Discussionmentioning
confidence: 99%
“…AtOMT3 is defined as AtASMT1, which increases melatonin levels, improves plant salt tolerance, and is closely related to Pst DC3000 resistance ( Shi, Wei & He, 2016 ; Zheng et al, 2017 ). AtOMT6 is an OMT protein on class II OMT protein that shows close homology with CmOMT8 and has been identified as AtCOMT1, which is associated with melatonin synthesis, regulating melatonin synthesis levels, and improving resistance to multiple stresses in plants, such as salt stress and heat stress ( Zheng et al, 2017 ; Hasan et al, 2023 ). In contrast, Chang et al (2021) reported that ClCOMT1 ( ClOMT3 ) is also closely homologous to CmOMT18 and could enhance abiotic stress resistance in Arabidopsis by increasing endogenous melatonin content.…”
Section: Discussionmentioning
confidence: 99%
“…ROS suppress carbon fixation by reducing the Calvin-Benson cycle enzymes' activity, resulting in reduced photosynthesis [10,11]. Recently, plant growth regulators have been broadly investigated as exogenous chemicals to reduce the damage caused by ROS, and thus promote photosynthesis, such as 5-aminolevulinic acid (ALA) [12,13], spermidine [14], and melatonin [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to direct response, there are other pathways through which cross-regulation and -response occur in plants under high-CO 2 conditions. For example, the melatonin content in tomato leaves is increased in a high-CO 2 environment, and endogenous melatonin levels affect the accumulation of sugars and starches [14]. Abscisic acid-deficient mutant plants show lower leaf stomatal conductance in a high-CO 2 environment than in normal conditions [15].…”
Section: Introductionmentioning
confidence: 99%